Project Based Learning to Improve Written Argumentation Skill of Tenth Graders - NOVIAN BUDI TAMA; RIEZKY MAYA PROBOSARI; SRI WIDORETNO; INDRIYATI INDRIYATI (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret, 2016)
The objectives of this research was to improve students written argumentation of the tenth grader of  science  class in a senior high school in Central Java through the aplication of projcet based learning. This research was a classroom action research conducted in three cycles. Each cycle consists of 4 stages, namely: planning, action, observing and reflecting. The subject of this research was 30 students in science class. The data of this research were obtained from test, observation and documentation. This research was descriptive qualitative research which was analyzed through three components: data reduction, data presentation, and taking the conclusion or verification. This research used a spiral model. The result shows that the aplication of project based learning improved students written argumentation skill, i.e. 22,04% in the pre-cycle, 30,48 in the  first cycle, 25,74% in the second cycle, and 32,01% in the third cycle. It can be said that the implemantation of project based learning can improve students' written argumentation skill in science class.